Discrete Centralized AGC Using LQR-Based Cost Functional Minimization for Multi-Area Interconnected Power Systems - Mohammed Esmail; Senthil Krishnamurthy (IEEE Access, 2024)
This paper proposes the design of Discrete Centralized Optimal Quadratic Automatic Generation Control (COQAGC) based on the functional minimization method (FMM) and optimal control theory for interconnected power systems. The cost function and FMM design requirements are defined in terms of area control errors, integral area control errors, and control signals. FMM is an optimal method, an easy and systematic approach for constructing and selecting state and control weighting matrices. The performance of COQAGC on discrete two-area interconnected power systems with identical _non-reheat thermal turbines has been studied using 1% and 5% step load perturbations (SLPs) and sensitivity analysis. The study has been extended to investigate the performance of COQAGC on discrete multi-area multi-source interconnected power systems with wind turbines. The simulation results revealed that developed COQAGC-based FMM improves the power system dynamics in terms of the steady-state performance and robustness against SLPs and parameter variations in comparison with controllers from the literature. The developed method can be extended and implemented on large complex multi-area power systems.